Foundations of educational technology : integrative approaches and interdisciplinary perspectives - Spector, J. Michael (New York : Routledge, 2012)
An engaging book for professional educators and an ideal textbook for certificate, masters, and doctoral programs in educational technology, instructional systems, and learning design, Foundations of Educational Technology, Second Edition offers a fresh, interdisciplinary, problem-centered approach to the subject, helping students build extensive notes and an electronic portfolio as they navigate the text. The book addresses fundamental aspects of educational technology theory, research, and practice that span various users, contexts, and settings; includes a full range of engaging exercises for students that will contribute to their professional growth; and offers the following four-step pedagogical features inspired by M. D. Merrill's First Principles of Instruction: Tell: Primary presentations and pointers to major sources of information and resources; Ask: Activities that encourage students to critique applications and share their individual interpretations; Show: Activities that demonstrate the application of key concepts and complex skills with appropriate opportunities for learner responses; Do: Activities in which learners apply key concepts and complex skills while working on practice assignments and/or projects to be created for their electronic portfolios. The second edition of this textbook covers the core objectives addressed in introductory educational technology courses while adding new sections on mobile learning, MOOCs, open educational resources, "big data," and learning analytics along with suggestions to instructors and appendices on effective writing, professional associations, and journals and trade magazines. -- from back cover.
Includes bibliographical references and index.
Keywords: Educational technology